Inflation Effect on Unemployment in Indonesia: A Comparative Studies Between Sharia and Conventional Economic Perspectives - Suharti, Sri; Naufal, Muhammad Dzaki; Paiman, Farah Ladina (JURNAL BISNIS STRATEGI, 2021)
This study discusses the effect of inflation on unemployment by comparing the perspective of Islam with capitalism. The purpose of this study is to identify the driving factors that cause inflation and unemployment. This research is conducted using descriptive analysis through linear regression analysis on Indonesia’s unemployment and inflation data from 2001 to 2019. This study found that inflation was not the main contributor to unemployment and only accounted for 18.6% of unemployment, whereas the remaining 80.4% was caused by other factors. This occurs because the increase in prices are not due to aggregate demand, but due to natural and man-made factors. To overcome inflation, the government should create policies to promoting a culture of saving, investing and discouraging wasteful and excessive spending from early age and improve the morale of officials and entrepreneurs. In addition to that, the government can also implement the law firmly and consistently to all parties who commit unethical behaviour; second, increasing the role of the community to observe and report corruption. To reduce the rate of unemployment, the government can implement several policies. Those are implementing policies that make it easier for startups to obtain capital, create investment security and facilitate licensing bureaucracy; second, providing more free and accessible work training courses, especially in urban areas; third, implement 12-year compulsory education consistently.